Traditional Calibration Methods in Atomic Spectrometry and New Calibration Strategies for Inductively Coupled Plasma Mass Spectrometry - Carter, Jake A.; Barros, Ariane I.; Nóbrega, Joaquim A.; Donati, George L. (Frontiers in Chemistry, 2018)
Applications, advantages and limitations of the traditional external standard calibration, matrix-matched calibration, internal standardization, and standard additions, as well as the non-traditional interference standard method, standard dilution analysis, multi-isotope calibration, and multispecies calibration methods are discussed.